Geofuels : energy and the earth - Carroll, Alan R. (Cambridge : Cambridge University Press, 2015)
Our energy use and its consequences (including climate change) motivate some of the most contentious and complex public debates of our time. Although these issues are often cast in terms of renewable versus non-renewable energy, in reality both depend on finite Earth resources. The evolution of the Earth itself therefore offers a uniquely illuminating perspective from which to evaluate alternative pathways toward energy and environmental sustainability. Geofuels: Energy and the Earth systematically develops this perspective using informal, nontechnical language laced with humor. It is well suited to a broad readership, ranging from beginning university students to lifelong learners who are interested in how the Earth's past will influence their own future. It also provides simplified explanations of controversial topics, such as energy return on energy investment, peak oil, and fracking. The focus throughout is on building a sound physical understanding of how natural resources constrain our use of energy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Power resources; Fossil fuels; Fossil fuels -- Environmental aspects; Renewable energy sources